2003
DOI: 10.1021/cm020599x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative XPS Study of Copper, Nickel, and Aluminum Coatings on Polymer Surfaces

Abstract: Two nitrogen-containing polymers, polyacrylonitrile and poly(styrene-co-acrylonitrile), and three oxygen-containing polymers, poly(vinyl methyl ether), poly(vinyl methyl ketone) and poly(methyl methacrylate), were coated with copper, nickel, and aluminum under ultrahigh vacuum, and their surfaces were analyzed by X-ray photoelectron spectroscopy. It was found that the morphology of the interface is mainly controlled by the properties of the metal, and, to a lesser extent, by the functionalities of the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 28 publications
6
46
0
Order By: Relevance
“…The appearance of TiC peaks in the X-ray photoelectron spectroscopy (XPS) spectra indicated covalent bonds between Ti atoms and C atoms in PMMA. XPS investigations by Bébin and Prud'homme of Ni nanofilms on PMMA showed that Ni reacted with the oxygen in the PMMA molecule [51]. This led to formation of nickel oxide, and a covalent bond at the metal-polymer interface.…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of TiC peaks in the X-ray photoelectron spectroscopy (XPS) spectra indicated covalent bonds between Ti atoms and C atoms in PMMA. XPS investigations by Bébin and Prud'homme of Ni nanofilms on PMMA showed that Ni reacted with the oxygen in the PMMA molecule [51]. This led to formation of nickel oxide, and a covalent bond at the metal-polymer interface.…”
Section: Resultsmentioning
confidence: 99%
“…The top electrode is produced only at a later stage, when the upper surface of the film is capped with a second layer of metal, evaporated in the same conditions as the lower electrode. Aluminum is preferred to other metals because of the sharpness of the interfaces between this element and several polymers [49]. Evaporated on top of a polymer film, gold, on the contrary, tend to diffuse through the organic medium.…”
Section: Nanocapacitors (Capped Films)mentioning
confidence: 99%
“…We did not consider varying the evaporation rate of the upper metallic layer, because this parameter would not affect the polymer-metal interface. Al, in fact, forms via weak dispersive forces very sharp interfaces when evaporated onto polymers and it does not diffuse into the polymer during the measurement time [27]. The fabricated nanocapacitors were placed in a dielectric cell and stabilized in a thermostat in a dry He atmosphere before investigation via an impedance analyzer (ModuLab XM MTS, Solartron Analytical), in a broad temperature and frequency range.…”
mentioning
confidence: 99%